PENGARUH KUALITAS PRODUK, HARGA DAN KETERSEDIAAN INFORMASI TERHADAP KEPUTUSAN BRAND SWITCHING HANDPHONE DI UNIVERSITAS STIKUBANK SEMARANG - Ari Susanti, 10.05.51.0043 (Students Journal of Economic and Management, 2014)
This study discusses the influence of product quality, price, availability of information on the behavior of consumers as well as the transfer of the trademark on what factors most influence the migration behavior of these brand. The purpose of this study was their influence is to examine the quality, price and availability of information on migration and examines the influence of the brand product quality, price and availability of information to influence the decision to move the brand to consumers. Techniques for determination of sample using purposive sampling techniques, namely choosing the appropriate sample with specific criteria.Respondents in this study of 100 respondents. Processing data in this study using palikasi SPSS (Statistical Package for Social Sciences). Include analysis of quantitative data analysis. Quantitative analysis includes testing the validity and reliability test, the classic assumption test, regression analysis, goodness of Fit test, coefficient of determination, the test statistic F, test statistik t. The results of this study indicate that the variable quality of the products tested negatively and significantly to brand switching. Variable pricing is positive and significant impact on brand switching. And the variable availability of information and no significant negative influence on brand switching. Keywords : Quality of Product, Price, Availability of Information, Brand Switching.